Strategi Ekstrakurikuler Muhadharah dalam Melatih Kemampuan Public Speaking Siswa Mi - Erfan Dwi Santoso; Rizki Amalia Sholihah; Yafita Arfina Mu’ti (Jurnal ini diterbitkan oleh: PGSD FKIP Universitas Muhammadiyah Tasikmalaya, 2021)
This study aims to determine the implementation of Muhadharah in training public speaking skills at MI Ruhul Amin, Muhadharah's extracurricular strategies in training public speaking skills, and its inhibiting and supporting factors. This type of research was conducted in the form of a qualitative descriptive field study. This study's sources of data include principals, teachers, students, and non-human data sources consisting of relevant madrasah documents and data. The results showed that the extracurricular activities of Muhadharah at MI Ruhul Amin were held every Saturday afternoon. The strategy used is to make a muhadharah schedule, compile and correct the speech's text, take turns choosing a place for muhadharah, take part in competitions or competitions. Inhibiting factors include students' lack of interest in muhadharah practice, lack of confidence, incomplete facilities, students' different character, and monotonous material delivery. These supporting factors include the extracurricular muhadharah that is carried out regularly, the existence of learning evaluations, the existence of sanctions for students who violate the rules, and quality supervisors